Influences of stack effect and longitudinal ventilation on the movement of buoyancy-driven contaminants in sloping tunnels. Issue 3 (September 2019) - Li, P; Du, T; Yang, D
Abstract: Sloping tunnels widely exist in mountainous regions and urban underground traffic systems. The dynamics of buoyancy-driven contaminants in a naturally ventilated slopping tunnel are generally different from that in a horizontal tunnel. Using the brine-water method and the light attenuation technique, we demonstrate that buoyancy-driven source location and source reduced gravity have significant influence on the steady-state density distribution in the sloping tunnel. The results suggest that the stack effect is an important factor influencing the movement of the buoyancy-driven flow in sloping tunnels. Subsequently, the dynamics of the buoyancy-driven flow in a longitudinally ventilated sloping tunnel are investigated. It is found that, under the combined effects of longitudinal ventilation and stack effect, multiple steady states exist for identical boundary conditions.